(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
This paper suggests a way in which quality media content should be properly used in education. More precisely, this paper suggests a way in which media content should be used as an educational resource. The term “media content” is herewith being elaborated in detail. The criteria for quality media content, as well as the great importance of quality educational content in the teaching process are emphasized. The term “educational resource” is defined, and we shall also present important statistical data related to this topic. А series of thematic educational films and media content will be thoroughly presented in this paper. Some of these films have been incurred during regular school classes, while some are a result from extracurricular activities, or are a part of student practice. The educational media content data base is created by the authors of this paper, nevertheless, this paper will also include media content from other authors or educational media productions. The opening of a media educational channel shall enable the establishment of an educational media content register, where teachers would have a clear insight into which unit/theme they would use media content. This type of educational resource is of a great importance for the realization of a high quality and modern teaching.